Environmental Orientation and Economic Performance: a Quasi‐experimental Study of Small Swedish Firms. (22nd August 2013) - Linder, Marcus; Björkdahl, Joakim; Ljungberg, Daniel
ABSTRACT This paper investigates the relationship between the environmental orientation and economic performance of small firms. We conduct a quantitative analysis on a sample of 299 environmentally oriented and all other small (2–49 employees) Swedish firms. We estimate the effect of environmental orientation on profit margin to examine how environmentally oriented firms perform in relation to non‐environmentally oriented firms. To do this, we employ a quasi‐experimental design in which we create a control group of non‐environmentally oriented firms that are very similar to their environmentally oriented counterparts. We use two measures of environmental orientation: (i) a third‐party classification, and (ii) a self‐assessment of environmental differentiation. The findings show a negative effect of environmental orientation on economic performance. Our contribution to the literature is in using a novel and more rigorous way to measure the relationship between environmental orientation and economic performance and providing implicit support for the existence of a causal link from economic performance to environmental orientation. Copyright © 2013 John Wiley & Sons, Ltd and ERP Environment